2015
DOI: 10.1088/0953-8984/27/25/255008
|View full text |Cite
|
Sign up to set email alerts
|

Light emission from Ag(111) driven by inelastic tunneling in the field emission regime

Abstract: Abstract. We study the light emission from a Ag(111) surface when the bias voltage on a scanning tunneling microscope (STM) junction is ramped into the field emission regime. Above the vacuum level, scanning tunneling spectroscopy (STS) shows a series of well defined resonances associated with the image states of the surface, which are Stark shifted due to the electric field provided by the STM tip. We present photonenergy resolved measurements that unambiguously show that the mechanism for light emission is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 38 publications
7
31
0
Order By: Relevance
“…Figure 1a shows the STS spectra (solid curves) of an Ag tip-Ag(111) junction with and without 633-nm excitation (hν=1.96 eV). The multiple peaks correspond to the series of the FERs which have been studied previously in the absence of illumination [19,20].…”
Section: Single Crystal Metal Surface Field Emission Resonancementioning
confidence: 92%
See 1 more Smart Citation
“…Figure 1a shows the STS spectra (solid curves) of an Ag tip-Ag(111) junction with and without 633-nm excitation (hν=1.96 eV). The multiple peaks correspond to the series of the FERs which have been studied previously in the absence of illumination [19,20].…”
Section: Single Crystal Metal Surface Field Emission Resonancementioning
confidence: 92%
“…The STML intensity is much higher for the Ag tip than Au most probably due to the weak plasmon damping of Ag. The cutoff wavelength (voltage) of the STML (plasmon excitation) is determined either by the quantum cutoff [19] that is simply the applied bias voltage (V s =3 V) or by the interband transition that is ~4 eV (~310 nm) and ~2.5 eV (~496 nm) for Ag and Au, respectively [22]. In Fig.…”
Section: Single Crystal Metal Surface Field Emission Resonancementioning
confidence: 99%
“…Electroluminescence induced by a tunnelling current across a metallic gap [16][17][18] , like that taking place in a Scanning Tunnelling Microscope (STM) junction [19][20][21][22][23][24][25][26][27][28][29][30][31] , has been also used as the feed driving light emission by plasmonic nanoantennas 32 . STM luminescence (STML) spectra, however, carry information not only on the optical properties of the structure but also on the energy distribution of the tunnelling electrons 19,20,[22][23][24][25][26][27][28][29][30] . Disentangling optical and electronic effects is an unsolved issue that limits the applicability of STML to the investigation of lightmatter interaction phenomena in nanocavities.…”
Section: Introductionmentioning
confidence: 99%
“…spectrum [68][69][70][71] (bottom inset of figure 2(a)) (details are found in the appendix 'Field emission resonances'). For measurements in the interval from 2 to 8 V, we extract regular tunneling ABHs ranging from 3.0 eV down to 0.5 eV, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The numbers indicate the reduction factor between 0.7 and 3.2 nm, which is the experimentally investigated interval. STM studies found a modification of the image potential energies due to the Stark shift caused by the static electric field between tip and sample [68,70].…”
Section: A4 Interferometric Autocorrelationmentioning
confidence: 99%